Verifiering av containervikter - Applicering av SOLAS krav på verifierade containervikter inom transportkedjan - Grip, Helmer; Skoog, Andreas (My University, 2016)
The container is today seen by many as the obvious choice for transporting larger volumes of cargo. However, the high efficiency has often resulted in careless handling with declarations resulting in numerous incidents where the ships stability and safety has been compromised. Despite weight declaration being legislated since 1968 in the Hague-Visby rules, inaccurate weight declarations have been an issue for a long time. ICS and WSC has published guidelines regarding the declaration of container weights, but without any legal significance. However, in 2014 IMO published new rules on verified container weights which where to commence worldwide the first of July, 2016. This report aims to find out how the players affected by the new legislation will have to respond to be able to comply with the new rules. The report also deals with how the players will be affected by the legislation in the form of reduced effectiveness and possible consequences for failing supervision. The result reveals some difficulties when the new rules are to be introduced since the legislation leaves much to decide to national authorities and the affected players. Current authority in Sweden is the Transport Agency, which among other tasks determines permissible variations between the declared weight and the actual weight. There is a general consensus amongst the players on how they will relate to the new rules. Verification will be provided by electronic means from the shipper via established information networks. In return the shipping companies do not see any need for checking if the shipper has used certified equipment. However, in the report presented there are some uncertainties around the new processes that might disrupt the flow of goods.
Keywords: Transportteknik och logistik; Transport; Transport Systems and Logistics; Transport